Long-term prognostic value of the combination of malnutrition and pulmonary-systemic pressure ratio in patients admitted with acute decompensated heart failure. (25th November 2020) - Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Tamaki, S; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Nakamura, J; Kayama, K; Fukunami, M
Abstract: Background: Malnutrition is associated with increased mortality risk in patients (pts) with acute decompensated heart failure (ADHF). On the other hand, concomitant presence of pulmonary hypertension in heart failure is associated with increased adverse events and may be related to interventricular uncoupling and impaired cardiac efficiency. It has recently been shown that an increased mean pulmonary artery pressure to mean systemic arterial pressure ratio (MPS ratio), a marker of interventricular coupling and efficiency, is associated with worse clinical outcomes in patients with advanced heart failure. However, there is no information available on the long-term prognostic value of the combination of malnutrition and MPS ratio in pts admitted for ADHF. Methods and results: We studied 248 pts admitted for ADHF, who underwent right heart catheterization at the admission and were discharged with survival. Malnutrition was assessed by geriatric nutritional risk index (GNRI), prognostic nutritional index (PNI) and controlling nutritional status score (CONUT). During a mean follow-up period of 5.2±4.4 yrs, 62 pts had cardiovascular death (CVD). MPS ratio was significantly greater in pts with than without CVD (0.408±0.114 vs 0.347±0.102, p=0.0001). GNRI and PNI were significantly lower, CONUT was significantly greater in pts with than without CVD. At multivariate Cox regression analysis, GNRI and MPS ratio were significantly associated with CVD, independently of prior heart failure hospitalization, eGFR, and serum sodium level and anemia, although PNI and CONUT showed the association with CVD at unvariate analysis. Pts with malnutrition (GNRI≤median value=96.5) and greater MPS ratio (≥median value=0.346) had a significantly higher CVD risk than those with either and none of them (51% vs 20% vs 12%, p<0.0001, respectively). Conclusions: The combination of malnutrition and MPS ratio might be useful for stratifying pts at risk for CVD in patients with ADHF. Funding Acknowledgement: Type of funding source: None